2014
DOI: 10.1074/jbc.m114.564450
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for the K+-dependent Na+/Ca2+-exchanger, NCKX4, in Melanocortin-4-receptor-dependent Satiety

Abstract: Background:The melanocortin-4 receptor, MC4R, regulates satiety, but the signaling mechanism is unknown. Results: K ϩ -dependent Na ϩ /Ca 2ϩ -exchanger, NCKX4, knock-out mice are lean and hypophagic and display MC4R-dependent, Ca 2ϩ -sensitive, constitutive activation of paraventricular nucleus neurons. Conclusion: Ca 2ϩ signaling is required for MC4R action, and its dysregulation in Nckx4 Ϫ/Ϫ mice leads to anorexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…SLC24A4 CpG methylation sites were also associated with Ab burden and tau pathology [83]. In a recent study, SLC24A4 knockout mice showed brain glucose hypometabolism [84]. Interestingly, we found a similar effect in NC.…”
Section: Discussionsupporting
confidence: 65%
“…SLC24A4 CpG methylation sites were also associated with Ab burden and tau pathology [83]. In a recent study, SLC24A4 knockout mice showed brain glucose hypometabolism [84]. Interestingly, we found a similar effect in NC.…”
Section: Discussionsupporting
confidence: 65%
“…Although it has been recently shown that MC4Rs in PVN neurons can activate a inwardly rectifying potassium channel (Kir7.1) via a G protein-independent mechanism (30), the role of this pathway in regulation of food intake and the identification of the specific PVN MC4R neuron population in which this pathway is operant has not been established. Studies have also established that MC4Rs are capable of activating Ca 2+ signaling, presumably via G q α and G 11 α, in cultured cell systems, including hypothalamic cells (15)(16)(17). We now show using an assay measuring IP 1 accumulation that a melanocortin MC3/4R agonist can induce PLC activity in the PVNs of control mice and that this effect requires G q/11 α, as IP 1 induction by MTII is absent in PVNGq/11KO mice.…”
Section: Discussionmentioning
confidence: 56%
“…Neither G q α KO (Gnaq -/-) (13) nor G 11 α KO (Gna11 -/-) (14) mice develop an obvious metabolic phenotype. MC4R signaling through G q/11 α has been documented in hypothalamic neurons (15)(16)(17), and cultured hypothalamic neurons have been documented to simultaneously generate both cAMP signals (via G s α) and PLC/Ca 2+ signals (via G q/11 α) (17). The dopamine D1 receptor was shown to differentially couple to G s α and G q/11 α in different brain regions (18).…”
Section: Introductionmentioning
confidence: 99%
“…␣MSH has been shown to cause increased cAMP levels in striatal brain slices, although it is unclear whether this response is due to direct actions of ␣MSH or whether it requires activation of D1R dopamine receptors (Cremer et al, 1998;Lezcano et al, 1995Lezcano et al, , 1993. Although MC3Rs and MC4Rs have been widely shown to couple to G s -proteins, a recent paper has demonstrated that ␣MSH can increase calcium in primary hypothalamic cultures and in GT1-7 cells through a process that involved phospholipase C and influx of extracellular calcium through TrpC channels (Li and Lytton, 2014). Thus, ␣MSH appears to be able to activate both the Gs-cAMP pathway and a pathway leading to increased calcium influx, both of which would be expected to be excitatory responses.…”
Section: Mechanisms Of ␣Msh Regulation Of Dopamine Pathwaysmentioning
confidence: 96%